The Ramsar's wise use concept in theory and practice: an investigation of the practice in Kolleru Lake, India, through a multidisciplinary approach - Senaratna Sellamuttu, Sonali; de Silva, Sanjiv; Nagabhatla, N.; Finlayson, C. Max; Pattanaik, C. (2010)
This paper highlights the dynamics between land use changes in the Kolleru Ramsar wetland and local livelihood systems and explains these through the lense of national policy responses and international (Ramsar) obligations. A multi-disciplinary approach was adopted by integrating geospatial tools and techniques with policy and livelihoods analysis. The findings show a temporal transfer of policy motives underpinning key land use changes, from agriculture supporting local livelihoods (up to the late 1970's) to maximizing economic values of land through commercial aquaculture (1980's-1999), and finally to ecological restoration and protection (1999 onwards). Each land use change brought new challenges at the local scale. Socio-economic assessments revealed that the demolition of aquaculture ponds (2006) prompted changes in livelihood strategies. Some households diversified their livelihoods (e.g. fishing)), while compensation packages helped this diversification in some instances. From the policy perspective, this case study illustrates the predominance of in-country/local lobbies over international obligations, in decision making for balancing ecosystem conservation with development.